Dança na Educação Básica: uma análise da produção de conhecimento à luz da teoria corpomídia - Silva, Edna Christine (2018)
This doctoral thesis' theme is dance teaching in primary education. Part of a long practical experience developed in the city of Juiz de Fora; and a bibliographical research that relates the area of communication, arts and pedagogy. It aims at analyzing the main issues which guide the pedagogical experiences, as well as their respective curricular guidelines. The main hypothesis is that the conception of body that substantiates the curricular bases has been fueled by traces of a Cartesian view, sparking a series of problems such as separation between theory and practice, reason and emotion, body and mind. Such debates generate a misguided view of dance teaching which, instead of being considered as an integral part of knowledge production, becomes mere entertainment. As theoretical foundation we started from bodymedia theory proposed by Katz and Greiner (2016) that admits the movement as the basis of thought, opening paths to consider dance teaching in primary education completely relevant. Moreover, we emphasize the necessity to construct a communicative ecosystem so that the school perceives the importance of the difference between thinking body and instrument body, from an approach between education and communication, as Martin-Barbero considers (2014). The research methodology was based on the construction of a dance panorama in the primary education showing pedagogical experience that happened in Brazil and some foreign countries. The expected result is the establishment of a discussion network, nationwide, to conduct to practical routes, in the eagerness of politicizing the debates and improve learning procedures from the uniqueness of the contexts where they are formed